Environmental and economic performance of innovative methods of growing plants (Eurasian Journal of Ecology, 2016)
The article is devoted to the comparison of economic and environmental efficiency cultivation methods in agriculture. this may lead to changes in environmental conditions in Kazakhstan, in the case of promotionof eco-efficient practices in agriculture.
Keywords: hydroponics; environmental effectiveness; efficiency